(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
The high serum uric acid concentration correlates with the degree of severity of the pregnancy induced hypertension (PIH) and perinatal outcome. In this context, maternal serum uric acid level is reported to be one of the prognostic factor for determination of perinatal outcome. Based on the existing data, the present prospective study was undertaken in the Department of Obstetrics and Gynaecology, BIRDEM Academy, from January to December, 2010. Out of 120 women, 60 suffering from PIH (severe preeclampsia and eclampsia) served as group I and 60 normotensive women at third trimester of pregnancy served as group II. This study showed that mean (±SD) serum uric acid was significantly elevated in group I PIH patients (7.21±1.81 mg/dl) compared to group II normotensive pregnancy (4.40±0.84 mg/dl). In group I PIH patients, 39 (86%) had adverse perinatal outcome (preterm, IUGR, stillbirth), and 6 (13.3%) term and healthy deliveries when serum uric acid level was >6 mg/dl. Current study showed that there was positive and statistically significant relationship between diastolic blood pressure and hyperuricaemia in group I PIH patients (r = +0.359, P<0.01). This study also showed that in group I PIH patients, when serum uric acid increased, birth weight significantly decreased (r = 0.279, P<0.05). J Bangladesh Coll Phys Surg 2014; 32: 124-129